(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Maloivan M. V. Information technologies based on the principles of individualization of self-education. The issue of individualization of self-education via information technologies is under consideration in this article. The article deals with the theoretical basement of the necessity of the individualization of the students’ self-study with the help of information technologies which activate their work during the educational process favouring the quality of education. Key words: individualization, self-studying, individualization of self-studying, principles of individualization, information technology.